Development of a framework for thermoeconomic optimization of simple and combined gas-turbine cycles - Aref, Pooneh (Cranfield University, 2012)
The problem consists of selecting simple and combined gas-turbine cycles with high thermal e±ciency and low capital cost is the subject of this study. In order to solve this problem, the so-called thermoeconomic optimization approach was used by se- lecting an appropriate objective function that combines the expenditures of ¯nancial resources (economic) and thermodynamic equations. Recently, a new de¯nition of objective function has been proposed to take into account environmental considera- tions as well. Thermoeconomic optimization is still an open research problem and currently under investigation. The present study is a part of ongoing research aimed at development of Techno-economical Environmental Risk Analysis (TERA) method- ology at Cran¯eld University for the evaluation of advanced power plant concepts in order to meet challenging environmental goals. The object of this work is to apply \design" and \operation" types of thermoeconomic optimization method to a simple and a combined gas-turbine cycle with pollution reduction. The optimization pro- cess adapts updated models for power demand patterns, legislation, capital cost, and in°ation. The outcome of study is the design of cost e±cient systems with reduced environmental impact. Cont/d.